Effects of Transcranial Direct Current Stimulation Combined with Rehabilitation for Upper Limb Function after Ischemic Stroke in Rehabilitation Center, Bach Mai Hospital - Hoai Thu, Bui Thi; Khanh, Luong Tuan; Thi Luyen, Le (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
Objective: evaluate effects of transcranial direct current stimulation (tdcs) combined with rehabilitation for upper limb function after ischemic. methods: the interventional study with the control group to evaluate effects of tdcs in upper limb function recovery programs in 20 ischemic stroke inpatients of the intervention group and 20 inpatients of the control group at the center rehabilitation of bach mai hospital from january 2020 to june 2020. results: the intervention group has the limb function on the arat scale increased 14,7%; and independence in daily activities according to barthel index improved 41 points and was higher than the control group, the barthel index change is statistically significant with p <0.05. there is no case recorded the side effects. conclusions: tdcs is safe and effective in recovering upper limb function and improving quality of life in ischemic patients. Keyword: Ischemic stroke, upper limb function, transcranial direct current stimulation. References